The Role of Steroidomics in the Diagnosis of Alzheimer's Disease and Type 2 Diabetes Mellitus - Vaňková, Markéta; Velíková, Marta; Vejražková, Daniela; Včelák, Josef; Lukášová, Petra; Rusina, Robert; Vaňková, Hana; Jarolímová, Eva; Kancheva, Radmila; Bulant, Josef; Horáčková, Lenka; Bendlová, Běla; et al. (International journal of molecular sciences, 2023)
Epidemiological studies suggest an association between Alzheimer's disease (AD) and type 2 diabetes mellitus (T2DM). This study aimed to investigate the pathophysiological markers of AD vs. T2DM for each sex separately and propose models that would distinguish control, AD, T2DM, and AD-T2DM comorbidity groups. AD and T2DM differed in levels of some circulating steroids (measured mostly by GC-MS) and in other observed characteristics, such as markers of obesity, glucose metabolism, and liver function tests. Regarding steroid metabolism, AD patients (both sexes) had significantly higher sex hormone binding globulin (SHBG), cortisol, and 17-hydroxy progesterone, and lower estradiol and 5α-androstane-3α,17β-diol, compared to T2DM patients. However, compared to healthy controls, changes in the steroid spectrum (especially increases in levels of steroids from the C21 group, including their 5α/β-reduced forms, androstenedione, etc.) were similar in patients with AD and patients with T2DM, though more expressed in diabetics. It can be assumed that many of these steroids are involved in counter-regulatory protective mechanisms that mitigate the development and progression of AD and T2DM. In conclusion, our results demonstrated the ability to effectively differentiate AD, T2DM, and controls in both men and women, distinguish the two pathologies from each other, and differentiate patients with AD and T2DM comorbidities.
Keywords: Alzheimer Disease; Diabetes Mellitus, Type 2; Alzheimerova nemoc; Androstenedione; komorbidita; androstendion; lidé; Female; Steroids; mužské pohlaví; Comorbidity; Male; diabetes mellitus 2. typu; steroidy; ženské pohlaví; Humans